2002
DOI: 10.1248/bpb.25.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the High Molecular Mass Fraction and Low Molecular Mass Fraction of Sho-saiko-to in a Murine Immunologically Induced Liver Injury Model.

Abstract: Many researchers have reported on the efficacies of Japanese and Chinese herbal remedies, so-called kampo-hozai. Since kampo-hozai are mixtures of plant and animal materials and contain numerous ingredients, most researchers have regarded each kampo-hozai as one drug for the investigation of the pharmacological actions using in vivo and in vitro systems. Alternatively, there have been many reports concerning the isolation and structure elucidation of major ingredients and the pharmacological and biochemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It is composed of seven herbs including Radix bupleuri, Radix scutellariae, Radix glycyrrhizae, Radix ginseng, Rhizoma pinelliae, Rhizoma zingiberis recens, and Fructus jujubae. Xiaochaihu Tang is widely used to treat chronic hepatitis [1][2][3], it also has cytoprotective effects in experimental liver injuries [4,5], preventive and therapeutic effects in experimental hepatic fibrosis via inhibition of hepatic stellate cells and lipid peroxidation in hepatocytes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of seven herbs including Radix bupleuri, Radix scutellariae, Radix glycyrrhizae, Radix ginseng, Rhizoma pinelliae, Rhizoma zingiberis recens, and Fructus jujubae. Xiaochaihu Tang is widely used to treat chronic hepatitis [1][2][3], it also has cytoprotective effects in experimental liver injuries [4,5], preventive and therapeutic effects in experimental hepatic fibrosis via inhibition of hepatic stellate cells and lipid peroxidation in hepatocytes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical and experimental studies have demonstrated the various pharmacological effects of SST. SST, a hot water extract of the mixture of seven medical herbs, is assumed to contain many LMC and HMC, and both groups of compounds have been demonstrated to have important pharmacological activities [49]. Phytochemical analysis of the LMC in the constituent herbs of SST has been performed by a number of investigators, and many LMC have been isolated, characterized, and proven to have biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been developed to remove HMC from Kampo medicines [17,49], and the method that is frequently used is as follows. SST is first dissolved in 10-fold weight of water and then ethanol is gradually added to its final concentration of 80% (v/v) aqueous ethanol.…”
Section: Separation Of Sst Into Fractions Of High and Low Molecular Cmentioning
confidence: 99%
See 1 more Smart Citation
“…SST, wogonin-7-O-glucuronoside (a major SST ingredient), and wogonin (an intestinal metabolite of wogonin-7-O-glucuronoside) increased CD4/CD8 ratio via a decrease of CD8+ T-cell counts with no effect on CD4+ T-cell counts (Ohtake et al, 2005). There is evidence suggesting that the high and low molecular mass fractions of SST act in a different manner, with the high molecular mass fraction suppressing the increase in plasma nitric oxide level in an LPS-induced endotoxin shock mouse model but the low molecular mass fraction lacking such activity (Nose et al, 2002).…”
Section: Discussionmentioning
confidence: 99%